2009
DOI: 10.2298/aci0901097h
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma in a horseshoe kidney

Abstract: A case of an adenocarcinoma within a horseshoe kidney (HK) is presented. Male patient presented with a history of a painless hematuria. A contrast enhanced magnetic resonance (MR) scan showed a horseshoe kidney. A large soft tissue mass was also noted on the right side. Kidney was receiving supply from two arteries on the left side and one at the right side. Angiography of the right renal artery demonstrated hypervascular tumor staining. The kidney was approached through midline abdominal incision, and a right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, the reported incidence in the literature is about 0.25%. [2] Horseshoe kidney is twice as common in males as in females. [1] No genetic determinant is known, although, it has been reported in identical twins and in siblings within the same family.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported incidence in the literature is about 0.25%. [2] Horseshoe kidney is twice as common in males as in females. [1] No genetic determinant is known, although, it has been reported in identical twins and in siblings within the same family.…”
Section: Discussionmentioning
confidence: 99%
“…So far only one case has been reported of surgical management of the horseshoe kidney in our country. The treated patient is still alive and with no signs of the recurrence of metastasis spread 4 .…”
Section: Characteristics Of the Tumor Of The Horseshoe Kidneymentioning
confidence: 91%
“…However, there have been only three recent case reports (including the present case) in which the contour and positional relationships among the renal parenchyma, tumor, and renal arteries were clearly identified. 2,4,5 In addition to the previous detailed discussion in the LPN era, there may be slight additional caution in the RAPN era. Tsivian et al 6 suggested that the choice of trans-or retroperitoneal approach depends on tumor location such as anterior, anterolateral, and isthmic locations that are suitable for the transperitoneal approach, whereas posterior and posterolateral tumors are suitable for the retroperitoneal approach; the same recommendations are applicable in the RAPN era.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…3 In the present case report, Fujihara et al reported the third successful case of RAPN for HSK. 4 The renal mass, which had a diameter of 2 cm in the lateral mid-pole of the left moiety, was resected using the transperitoneal RAPN procedure.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation